Upaya Peningkatan Sifat Mekanik Baja Mild Steel Melalui Perbaikan Kualitas dengan Heat Treatment Annealing dan Holding Time pada Heat Treatment dengan Taguchi Method - Rahmadianto, Febi; Purnowidodo, Anindito; Soenoko, Rudy (Jurnal Rekayasa Mesin, 2014)
The purpose of this study was to determine the ability of the mechanical tensile strength and hardness and microstructure of the steel material Mild Steel. The electrodes used were a new electrode, the electrode was added calium compound is then heated to 100 °C, 100 ° C and heated electrode. Strong currents are used 75 A, 85 A, and 95 A, for a distance of specimen 3 mm, 4 mm and 5 mm. This study used an experimental methodology and the research conducted in the laboratory. The test results showed that the maximum tensile strength is in the condition of the electrode plus a calium compound and heated at 100 ° C, 95 A current and a distance of 5 mm , with Heat Treatment 20 minutes is 278 N/mm2 . Similarly , for the region of weld metal hardness indicates the optimal hardness using electrodes were added and heated calium compounds 100oC , current 95 A and a distance of 5 mm , with Heat Treatment 20 minutes , which is 185 VHN . HAZ hardness to areas with the same test conditions with Weld Metals, hardness value is 371 VHN.Keywords: SMAW, current, Taguchi, optimum treatment.